2020
DOI: 10.34117/bjdv6n10-013
|View full text |Cite
|
Sign up to set email alerts
|

Plantas Medicinais Usadas Por Comunidades Ribeirinhas Do Estuário Amazônico / Medicinal Plants Used by Riverside Communities in the Amazon Estuary

Abstract: RESUMO O uso de plantas medicinais faz parte da cultura de diferentes comunidades amazônicas. Este estudo efetua uma análise do uso e importância das plantas medicinais em duas comunidades ribeirinhas da Ilha das Onças, Barcarena-PA, visando contribuir para o resgate e preservação do conhecimento popular local. Foram realizadas entrevistas semiestruturadas com dez famílias selecionadas por amostragem não probabilística (Bola de Neve), indicadas através de um informante principal e utilizados formulários para c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…For the preparation process, several parts of the vegetables were cited, highlighting, considerably, the Leaves, with 80.0% of the occurrences (Figure 2). Several studies have shown similar results, always bringing leaves as the main part used 25,35,36,37,38 . For Battisti et al 39 , the likely explanation for this is because the leaves are easy to collect and always available throughout the year.…”
Section: Sociodemographic Datamentioning
confidence: 66%
“…For the preparation process, several parts of the vegetables were cited, highlighting, considerably, the Leaves, with 80.0% of the occurrences (Figure 2). Several studies have shown similar results, always bringing leaves as the main part used 25,35,36,37,38 . For Battisti et al 39 , the likely explanation for this is because the leaves are easy to collect and always available throughout the year.…”
Section: Sociodemographic Datamentioning
confidence: 66%
“…The Amazon has great biological and sociocultural diversity, represented by indigenous peoples and traditional populations, who have an invaluable collection of traditional knowledge about regional biodiversity (Marques, Anjos, & Costa, 2020). Conducting studies with plants used by these ethnic groups and in traditional medicine is considered a priority in the Brazilian Amazon due to the great richness of its flora, which can be used to obtain antimicrobial substances (Pereira, Santos, Rodrigues, Andrade, & Guimarães, 2020).…”
Section: Introductionmentioning
confidence: 99%